Assessing causal associations of hyperparathyroidism with blood counts and biochemical indicators: a Mendelian randomization study - Jiang, Yan; Chen, Rumeng; Xu, Shuling; Ding, Yining; Zhang, Mengling; Bao, Meihua; He, Binsheng; Li, Sen (Frontiers in Endocrinology, 2023)
The exis ng literature on the rela onship of hyperparathyroidism with both blood counts and biochemical indicators primarily comprises observa onal studies, which have produced inconsistent findings. The aim of this study is to evaluate the causal rela onship between hyperparathyroidism and blood counts and biochemical indicators. Methods:Mendelian randomiza on (MR) analyses were conducted to inves gate the associa ons between hyperparathyroidism and the iden fied 55 blood counts and biochemical indicators.The genome-wide associa on study (GWAS) for hyperparathyroidism data was obtained from FinnGen, while the GWASs for the blood counts and biochemical indicators were sourced from the UK Biobank (UKBB). Results: The MR analysis using the inverse-variance weighted (IVW) method revealed poten al causality between gene cally predicted hyperparathyroidism and seven out of 55 blood counts and biochemical indicators. These markers include "Platelet count" (Beta = -0.041; 95% CI: -0.066, -0.016; p = 0.001), "Platelet distribu on width (PDW)" (Beta = 0.031; 95% CI: 0.006, 0.056; p = 0.016), "Mean platelet volume (MPV)" (Beta = 0.043; 95% CI: 0.010, 0.076; p = 0.011), "Vitamin D" (Beta = -0.038; 95% CI: -0.063, -0.013; p = 0.003), "Calcium (Ca 2+ )" (Beta = 0.266; 95% CI: 0.022, 0.509; p = 0.033), "Phosphate" (Beta = -0.114; 95% CI: -0.214, -0.014; p = 0.025), and "Alkaline phosphatase (ALP)" (Beta = 0.030; 95% CI: 0.010, 0.049; p = 0.003). Conclusion: The findings of our study revealed a sugges ve causal rela onship between hyperparathyroidism and blood cell count as well as biochemical markers. This presents a novel perspec ve for further inves ga ng the e ology and pathological mechanisms underlying hyperparathyroidism.